Asian Wild Elephants (Elephas maximus) in Eastern Nepal - Yadav, Babu Ram (Nepal Journal of Forestry, 2008)
Jhapa, Morang, Sunsari, Saptari & Udayapur districts of Nepal and Darjeeling, India were selected for the study of the migration of wild elephants in the study areas. The number of the small and big herds varied 12-13 and 50-74 respectively. The big herds raid crops in Bahundangi Village Development Committee and Darjeeling district of India, whereas the small herd raids crops from Jhapa to Udayapur disricts. Since the last 15 years Asian wild elephants have demolished more than 277 houses and killed more than 66 people in eastern Nepal. Farmers have also killed more than 23 elephants in above districts in order to protect their crops and property. Trans-boundary cooperation meetings between Nepal and India should continue. In addition, creation of new protected areas, and expansion of the existing Koshi Tappu Wildlife Reserve to Trijuga forest will be necessary. An action research project on wild elephant conservation should be implemented by attracting the international and national conservation partners.